2014
DOI: 10.4049/jimmunol.1302663
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Ig and Mucin Domain–Containing Protein 3 Is Recruited to the Immune Synapse, Disrupts Stable Synapse Formation, and Associates with Receptor Phosphatases

Abstract: CD8+ cytotoxic T lymphocytes (CTL) are adept at killing virally infected cells and cancer cells and releasing cytokines (e.g. IFN-γ) to aid this response. However, during cancer and chronic viral infections, such as with Human Immunodeficiency Virus, this CTL response is progressively impaired due to a process called T-cell exhaustion. Previous work has shown that the glycoprotein, T-cell immunoglobulin and mucin domain-containing protein 3 (Tim-3) plays a functional role in establishing T-cell exhaustion. Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 48 publications
4
94
0
Order By: Relevance
“…Importantly, the analogous tyrosines in human Tim-3 also scored as possible sites of phosphorylation by the same classes of kinases (not shown). We and others have demonstrated that the cytoplasmic tail of Tim-3 can indeed be phosphorylated on multiple tyrosine residues (35, 43, 44). While the identity of the kinases that phosphorylate the Tim-3 cytoplasmic tail have not been definitively shown in vivo, our data are consistent with such phosphorylation being carried out by the Src family kinases Fyn and/or Lck, at least in T cells (35).…”
Section: Tim-3 Proximal Signaling – Tyrosine Kinases and Beyondmentioning
confidence: 84%
See 1 more Smart Citation
“…Importantly, the analogous tyrosines in human Tim-3 also scored as possible sites of phosphorylation by the same classes of kinases (not shown). We and others have demonstrated that the cytoplasmic tail of Tim-3 can indeed be phosphorylated on multiple tyrosine residues (35, 43, 44). While the identity of the kinases that phosphorylate the Tim-3 cytoplasmic tail have not been definitively shown in vivo, our data are consistent with such phosphorylation being carried out by the Src family kinases Fyn and/or Lck, at least in T cells (35).…”
Section: Tim-3 Proximal Signaling – Tyrosine Kinases and Beyondmentioning
confidence: 84%
“…Another recent study examined the interaction of Tim-3 with transmembrane proteins expressed on T cells, and reported that Tim-3 can associate with the transmembrane phosphatases CD45 and CD148, which the authors proposed might promote de-phosphorylation of downstream mediators of T cell activation (44). Furthermore, Tim-3, CD45 and CD148 were all found to be recruited into the immunological synapse.…”
Section: Tim-3 Proximal Signaling – Tyrosine Kinases and Beyondmentioning
confidence: 99%
“…3): first, by ectodomain competition, which refers to inhibitory receptors sequestering target receptors or ligands and/or preventing the optimal formation of microclusters and lipid rafts (for example, CTLA4 (REF. 31)); second, through modulation of intracellular mediators, which can cause local and transient intracellular attenuation of positive signals from activating receptors such as the TCR and co-stimulatory receptors 3234 ; and third, through the induction of inhibitory genes 14 .…”
Section: Developmental Pathways Of Exhaustionmentioning
confidence: 99%
“…45,[59][60][61] We and others have observed that Tim-3 + CD8 + T cells are increased in progressive HIV infection, and engagement presumably through a Gal-9 interaction leads to CD8 + T cell dysfunction. 33,60,62,63 During chronic HIV infection, Gal-9-expressing Treg cells are presumed to selectively suppress the proliferation of nonprotective HIVspecific CD8 + T cells with high Tim-3 levels, but not protective HIV-specific CD8 + T cells with low levels of Tim-3. 64 Soluble Gal-9 levels have been shown to be elevated in the plasma of HIV-infected subjects, [64][65][66] suggesting that Gal-9 may play an important role in HIV pathogenesis.…”
Section: Introductionmentioning
confidence: 99%